Full text in PDF for the SOSIOHUMANIKA Journal, issue of May 2011 - SOSIOHUMANIKA, Editor Journal (ASPENSI in Bandung, Indonesia, 2011)
This journal was firstly published on May 20, 2008 by ASPENSI (Asosiasi Sarjana Pendidikan Sejarah Indonesia or Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The SOSIOHUMANIKA journal is published twice a year i.e. every May and November.Â